2016
DOI: 10.1186/s40360-016-0101-x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity and nephrotoxicity caused by combined use of lithium and risperidone: a case report and literature review

Abstract: BackgroundCombination lithium, a mood stabilizer, and risperidone, an atypical antipsychotic drug, is widely used for treatment of psychotic disorders. Rare reports concern severe adverse drug reaction in multiple organic systems with their combined use. We report two episodes of neurotoxicity and nephrotoxicity in a patient following the combined use of lithium and risperidone.Case presentationA 55-year-old male had a diagnosis of schizoaffective disorder at the age of 51. He was initially treated with a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
12
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 18 publications
4
12
0
8
Order By: Relevance
“…Cr and BUN were the classical standards to evaluate renal damage (34). Accordingly, Hsu et al demonstrated the observation of elevated Cr in an atypical antipsychotic drug administration (35). The current study demonstrates that OLZ exposure produced a significant increase in the levels of Cr and BUN indicating damaged structural and functional kidney integrity.…”
Section: Discussionmentioning
confidence: 48%
“…Cr and BUN were the classical standards to evaluate renal damage (34). Accordingly, Hsu et al demonstrated the observation of elevated Cr in an atypical antipsychotic drug administration (35). The current study demonstrates that OLZ exposure produced a significant increase in the levels of Cr and BUN indicating damaged structural and functional kidney integrity.…”
Section: Discussionmentioning
confidence: 48%
“…Lityum, risperidon ve ketiapin dopamin nörotransmisyonunun bileşenlerini modüle etmektedirler (9,10,13). Lityum presinaptik dopamin salınımını önleyerek, risperidon ve ketiapin ise dopamin reseptörlerini bloke ederek etki gösterirler (8,13). Lityum ve risperidon arasındaki ilaç etkileşiminden kaynaklanan nörotoksisitenin iki hipotezi vardır.…”
Section: Discussionunclassified
“…Birincisi risperidondan bağımsız sadece lityum intoksikasyonuna bağlı nörotoksisitedir. İkincisi ise, hem lityum hem de risperidonun dopamin reseptör blokajını arttırarak nörotoksisiteye yol açmasıdır (8,13). Risperidonu diğer antipsikotik ilaçlarla karşılaştıracak olursak, lityumla kombinasyonunda nörotoksik semptomların gelişme riskinin daha yüksek olduğu belirtilmektedir (13).…”
Section: Discussionunclassified
See 2 more Smart Citations